A policy-based quality of service management system for IP DiffServ networks. - Flegkas, P.
Policy-based management can guide the behavior of a network or distributed system through high-level declarative directives that are dynamically introduced, checked for consistency, refined, and evaluated, resulting typically in a series of low-level actions. We actually view policies as a means of extending the functionality of management systems dynamically, in conjunction with preexisting hard-wired management logic. We first discuss the policy management aspects of architecture for managing quality of service in IP DiffServ networks as presented by Trimintzios et al. (see IEEE Commun. Mag., Special Issue in IP Operations and Management, vol.39, no.5, p.80-88, 2001), and focus on the functionality of the dimensioning and resource management aspects. We then present an analysis of the policies that can influence the dimensioning behavior as well as the inconsistencies that may be caused by the introduction of such policies. Finally, we describe the design and implementation of the generic policy consumer component and present the current implementation status
Keywords: IP DiffServ networks; Internet; Distributed system; Generic policy consumer component; Hard-wired management logic; Network architecture; Network dimensioning; Network system; Object-oriented information model; Policy information model; Policy-based QoS management system; Quality of service; Resource management